Pre-operative Plasma Levels of Thrombin-Antithrombin III Complexes Correlate with the Development of Venous Thrombosis after Major Hip or Knee Surgery - Ginsberg, Jeffrey S; Brill-Edwards, Patrick; Panju, Akbar; Patel, Ameen; McGinnis, Joanne; Smith, Frank; Dale, Ian; Johnston, Marilyn; Ofosu, Fred (Thrombosis and Haemostasis, 1995)
Study objective. To determine whether levels of thrombin-antithrombin III (TAT) in plasma, taken two weeks pre-operatively, predict the development of deep vein thrombosis (DVT) in patients undergoing major hip or knee surgery.Design. Prospective cohort.Setting. Tertiary-care referral centre, university-affiliated hospital.Patients. Ninety eight consecutive patients undergoing elective hip or knee surgery.Intervention. All eligible consenting patients were seen in a preoperative clinic two weeks prior to surgery and had blood taken for measurement of plasma TAT level. After surgery, they received a combination of unfractionated heparin 5000 Units 12-hourly subcutaneously, and antiembolism stockings (TEDS), as prophylaxis against DVT. Contrast venography was performed prior to discharge, and according to the results, patients were classified as having proximal (popliteal and/or more proximal) DVT (n = 12), calf DVT (n = 7) or no DVT (n = 79).Measurements and Results. The mean TAT level was significantly higher in patients who developed DVT (5.7 μg/l) than in those who did not (4.1 μg/l), p = 0.035. Using cut-points of 3.5 and 5.5 μg/l for the TAT level, patients could be categorized as high, intermediate, and low risk for the development of DVT. The proportion of patients with TAT levels of ≥3.5μg/l who developed calf or proximal DVT was significantly higher than the proportion of patients with TAT levels of <3.5 μg/l who developed calf or proximal DVT (p = 0.02). The proportion of patients with TAT levels >5.5 μg/l who developed proximal DVT was significantly higher than the proportion of patients with TAT levels of ≤5.5 μg/l who developed proximal DVT (p = 0.03).Conclusions. This study demonstrates that pre-operative TAT levels correlate with the risk of developing DVT after major orthopedic surgery. Further studies are needed to determine the reason(s) for this observation and whether rational recommendations about prophylaxis and screening for DVT can be made based on the results of a pre-operative TAT level.